(untitled) (GYMNASIUM, 2010)
In the present production, the electronic industry pertains to the most important branches of the present economy. Also, the physical and professional-applicative training of the students of the speciality technical professional schools, at the conceptual-educational level, is presented only through the general statements, reflected in "School Curricula for Senior High Schools" (2006), which "apply also in the 12th grade - technological field, progressive qualification route through the arts and crafts schools + additional year". The practice of high school teaching in the technical-electronic field demonstrates that in this field, up until now, the issues related to the specification of the content and of the physical education organization process have yet many issues unsolved.